Implementation of Ta'awun and Sadd Dzari'ah concepts in Mutabarok Bunda Sejahtera Financing at PT. BPRS Magetan - Wedi Pratanto Rahayu; Muammar Al Fikri; Guijiao Zou; Lie Jie; Cai Jixiong (Rechtsnormen: Journal of Law, 2023)
Background. The importance of conducting this research is because the function and role of Islamic banks does not only solves the capital needs of society, but the practice is in accordance with the constitution and to realize the benefit of society. As contained in this Mutabarok Bunda Sejahtera financing. This financing is not only a solution to the capital needs of small traders but also applies the concept of ta’awun and sadd dzari’ah. Purpose. This research aims to know the implementation of the concept of ta’awun and sadd dzari’ah in the practice of Mutabarok Bunda Sejahtera financing at PT BPRS Magetan. Method. The type of research used in this research is a type of qualitative research, namely research that explores the implementation of a concept applied in the field, namely the implementation of the concept of ta'awun and sadd dzari'ah in Mutabarok Bunda Sejahtera Financing at PT. Results. PT BPRS Magetan is one of the banks in the form of a Limited Liability Company in Magetan Regency, East Java Province, which is based on a sharia system with the largest shares owned by the Magetan Regency Government. Conclusion. Its existence is very helpful to the economy of the people of Magetan Regency, through the activities of raising funds and channeling funds, so that the rotation of the economy of the community can run.